Monitoring the Agri-food System in Myanmar: The rising costs of diets – March 2024 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
This research note presents the results of 26 rounds of interviews with food vendors in rural and urban areas throughout Myanmar conducted between June 2020 and March 2024. The purpose of the surveys is to provide data and insights on Myanmar’s food markets to interested stakeholders to foster better understanding of the effects of shocks related to COVID-19 and the ongoing political crisis. The focus of this research note is on changes in food prices and the cost of common and healthy diets.